Health and carcinogenic risk evaluation for cohorts exposed to PAHs in petrochemical workplaces in Rawalpindi city (Pakistan). Issue 1 (2nd January 2016) - Kamal, Atif; Cincinelli, Alessandra; Martellini, Tania; Palchetti, Ilaria; Bettazzi, Francesca; Malik, Riffat Naseem
Abstract : This study presents the analyses of urinary biomarkers (1-OHPyr, α- and β-naphthols) of polycyclic aromatic hydrocarbons (PAHs) exposure and biomarkers of effect (i.e. blood parameters) in petroleum-refinery workers (RFs) and auto-repair workers (MCs). Exposed subjects had higher concentrations of white blood cell (WBC) count than control subjects (CN) subjects (5.31 × 10 3 μL −1 in exposed vs. 5.15 × 10 3 μL −1 in CN subjects), while the biomarker of oxidative DNA damage (8-OHdG) was significantly higher in MCs. The exposure among these two cohorts could be influenced by the ambience of the workplaces; in fact, MCs' shops are relatively damp and enclosed workplaces in comparison with the indoor environment of refineries. PAHs in the dust samples from mechanical workshops probably originated from mixed sources (traffic exhaust and petroleum spills), while the incremental lifetime cancer risk (ILCR) for MCs showed moderate-to-low cancer risk from exposure to dust-bound PAHs. The study shows that increasing PAH exposure can be traced in MC workstations and needs to be investigated for the safety of public health.